1984
DOI: 10.1073/pnas.81.8.2308
|View full text |Cite
|
Sign up to set email alerts
|

A large interspersed repeat found in mouse DNA contains a long open reading frame that evolves as if it encodes a protein.

Abstract: DNA sequence analysis of a region contained within a large, interspersed repetitive family of mice reveals a long open reading frame. This sequence extends 978 base pairs between two stop codons, creating a reading frame that is open for 326 amino acids. The DNA sequence in this region is conserved between three distantly related Mus species, as well as between mouse and monkey, in a manner that is characteristic of regions undergoing selection for protein function.Interspersed repetitive elements are ubiquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…Therefore, in this way the rat LINE family is similar to the mouse and primate LINE families, which also contain ORFs (33,53). Martin et al (33) showed that the ORFs in mouse LINE sequences have evolved like bona fide protein-encoding sequences; i.e., silent base changes (no amino acid change) are more prevalent than replacement base changes. This is also true of ORF4 and its counterparts in the other rat LINES.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this way the rat LINE family is similar to the mouse and primate LINE families, which also contain ORFs (33,53). Martin et al (33) showed that the ORFs in mouse LINE sequences have evolved like bona fide protein-encoding sequences; i.e., silent base changes (no amino acid change) are more prevalent than replacement base changes. This is also true of ORF4 and its counterparts in the other rat LINES.…”
Section: Methodsmentioning
confidence: 99%
“…Other workers have suggested that all of the primate or mouse LINE ORFs examined to date are pseudogenes (33,53) or relics of the intact (longer) ORF(s) present in the few functional progenitor LINE family members from which most present-day nonfunctioning LINE members were derived (14,43,55,59,60 (Fig. 4) that was hybridized to total liver nuclear RNA, prepared, and radiolabeled with [_y_12P]ATP and polynucleotide kinase as described previously (65).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The proteins predicted by the ORFs include regions with homology to reverse transcriptase and nucleic acid-binding proteins (19,24,36).Li elements in other mammals are similar to those in primates with regard to abundance and overall organization (3,19,20,33,36,37,50,60,63). Moreover, both the nucleotide sequence of the ORF region and the polypeptides predicted from the ORFs are homologous in all mammalian orders that have been analyzed.…”
mentioning
confidence: 98%
“…About 95% of the sequence was determined in both directions or from a series of overlapping Exolll deletion clones (11). Open reading frames have been identified in the corresponding region of mouse LINEs and primate LINEs (19) and thus appear to be a general feature of mammalian LINEs. We analyzed all of the non-LINE insulin 1 sequence for homology to all segments of the rat LINE diagrammed in Fig. 6 by computer methods suitable for detecting either general or local regions of homology.…”
mentioning
confidence: 99%